Portraying the Use of Conversation Simulation in Indonesian Speaking Classroom - Roizul A'la; Oktavia Widiastuti; Maria Purnawati (JURNAL DIMENSI, 2026)
This study aims to describe the vocational speaking English learning process of eleventh-grade students at a vocational high school in Malang through the implementation of the conversation simulation method. Many EFL students face difficulties in speaking English due to limited vocabulary, low confidence, and lack of opportunities for real communication. This study employed a descriptive qualitative approach using classroom observations and interviews as the data sources. The findings show that conversation simulation increased students’ classroom interaction and improved their speaking performance, including fluency, pronunciation, vocabulary, and confidence. Moreover, the classroom atmosphere became more active and communicative. This study concludes that conversation simulation is an effective method to support students’ vocational English development and enhance classroom interaction.